Ultra-Processed Foods and Metabolic Dysfunction: Mechanisms, Clinical Implications, and Public Health Perspectives. Position Paper of the Italian Association of Dietetics and Clinical Nutrition (ADI) - Giovanna Trinchese; Barbara Paolini; Fabiano Cimmino; Filippo Valoriani; Lucio Lucchin; Carmela Bagnato; Annarita Sabbatini; Massimiliano Petrelli; Pietro Losignore; Francesca Marino; Giulia Tavella; Sebastiano Banni; et al. (Current Nutrition Reports, 2026)
Abstract Purpose of Review This position paper by the Italian Association of Dietetics and Clinical Nutrition (ADI) evaluates the impact of ultra-processed foods (UPFs) on metabolic health and chronic disease risk, with particular attention to the biological and behavioural mechanisms involved. Recent Findings High UPFs consumption has been associated with obesity, insulin resistance, cardiovascular disease, metabolic dysfunction-associated steatotic liver disease (MASLD), cancer, neuroinflammation, and immune dysregulation. Proposed mechanisms include gut microbiota alterations, increased intestinal permeability, mitochondrial dysfunction, oxidative stress, impaired metabolic flexibility, and chronic low-grade inflammation. The hyperpalatable nature of UPFs may also impair appetite regulation and promote overconsumption, especially among children and adolescents. Additional concerns involve food additives, processing-derived contaminants, and endocrine disruptors from packaging materials. Summary Current evidence identifies UPFs as a major modifiable risk factor for non-communicable chronic diseases. Reducing UPFs exposure should therefore represent a public health priority, supported by preventive nutritional strategies, improved food classification systems, and targeted educational and regulatory interventions. Graphical Abstract Graphical Abstract. Ultra-Processed Food Consumption and metabolic dysfunction mechanisms. The high consumption of ultra-processed foods (UPFs) containing refined ingredients, additives, emulsifiers, and artificial flavouring agents lead to an increased intestinal permeability and dysbiosis. These alterations together with mitochondrial dysfunction and metabolic inflexibility lead to chronic low-grade inflammation. Furthermore, the high palatability of ultra-processed foods triggers hedonic eating mechanisms and encourage overconsumption. The interplay between microbiota-related altered metabolic signalling, increased adiposity and inflammatory processes contributes to an endocrine and metabolic disruption. These mechanisms may be particularly important during critical stages of development, such as childhood and adolescence, when dietary exposure can influence long-term metabolic programming and increase the risk of developing metabolic diseases later in life. Figure created with BioRender.com